Order-disorder transition-induced band nestification in AgBiSe2–CuBiSe2 solid solutions for superior thermoelectric performance. Issue 8 (21st December 2020) - Jang, Hanhwi; Abbey, Stanley; Nam, Woo Hyun; Frimpong, Brakowaa; Nguyen, Chien Viet; Joo, Sung-Jae; Shin, Ho Sun; Song, Jae Yong; Cho, Eugene N.; Kim, Moohyun; Jung, Yeon Sik; Oh, Min-Wook
Abstract : The AgBiSe2 –CuBiSe2 system shows band nestification at high temperatures, resulting in heavy DOS effective mass while preserving electron mobility. Abstract : Despite the fact that research into most high-performance thermoelectric (TE) materials is focused on tellurides, compelling demand has arisen to replace tellurium (Te) with selenium (Se) due to the scarcity of Te. Silver bismuth diselenide (AgBiSe2, ABS) has been widely studied in relation to thermoelectric applications due to its intrinsically low thermal conductivity. However, its low power factor (PF) has been considered as an underlying issue preventing improvements of the TE properties of ABS. Here, it is demonstrated that a high PF can be achieved by incorporating Cu into the ABS system via the nestification of conduction bands when a disordering between Ag and Bi occurs. Degenerate electronic bands simultaneously increase the density-of-states effective mass and carrier concentration while not reducing the carrier mobility significantly. Therefore, improved TE performance with a maximum PF of 8.2 μW cm −1 K −2 and a peak zT value of 1.14 was achieved at 773 K, opening a new horizon for the development of environmentally benign TE materials with high performance capabilities.